Strategi Komunikasi Tenaga Kesehatan melalui Program Promosi Kesehatan - Destiwati, Rita; Wafa, Uyun (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study discusses the communication role of health workers in health promotion programs at Puskesmas Gegesik, Cirebon. Health workers have dual roles as nurses and health promoters, which are sometimes less effective in achieving program targets. Awareness of the need for specialized public health experts for targeted health promotion programs is the focus of this study. This qualitative research used interviews, observation, and documentation to determine health workers' communication strategies. The results showed that health workers at Puskesmas Gegesik have implemented effective communication strategies, such as recognizing targets, choosing media, determining message objectives, and understanding their role as communicators. This significantly improves public health efforts and achieves health promotion program targets.